The Function of Indonesia Government in Bridge the Performance of MSMEs during the Covid-19 - Jiuhardi Jiuhardi; Adi Wijaya; Nurjanana Nurjanana; Mutiara Kartika Dewi (Budapest International Research and Critics University, 2022)
The urgency of this paper is to expose the performance of the Indonesian government to encourage and stimulate the existence of MSMEs because of the economic crisis caused by Covid-19. The paper method uses the document study method based on the results of previous research, which is traced through journals of several electronic media, such as digital libraries, websites, and library journal connections. We carried journal searches out via Google Browser and Google Scholar. It carried journal searches out using keywords in MSMEs, the role of the Indonesian government, and the economy of the Covid-19. From each research result got, it is further analyzed, which is then used as a supporting journal to strengthen that the Indonesian government plays a role in improving performance of micro, small and medium enterprises. The Indonesian government has a policy to handle micro, small and medium enterprises in Indonesia. The regulates state financial policies, including state revenue, including policies in taxation, state expenditure policies, including policies in regional finance, and financing policies. Indonesia allows MSME business activities to be a guarantee for accessing business financing loans and government also provides a Special Allocation Fund (DAK) to support the empowerment and development of MSMEs.